The effect of consumer ethnocentrism on the acceptance of imported grocery products in Harare, Zimbabwe - Charity Muchandiona (Taylor & Francis Group, 2021)
The study investigated the effect of consumer ethnocentrism on the acceptance of imported grocery products in Harare, Zimbabwe. Using a cross-sectional survey of 505 consumers, independent-samples T-test, analysis of variance and structural equation modelling were used to test research hypotheses. Results show that gender, age and education significantly influence consumer ethnocentrism. Income was found to have an insignificant influence on consumer ethnocentrism. Results also show that consumer ethnocentrism had a negative effect on consumer attitude towards imported grocery products. Consumer attitude was found to have a positive effect on consumer intention to buy imported grocery products. Similarly, consumer ethnocentrism was found to negatively influence consumer’s intention to purchase imported grocery products while consumer’s intention was found to positively influence consumer’s actual purchase behaviour towards imported grocery products. These findings have theoretical and practical implications.